Cover Image. (June 2018) - Altaf, Ataf A.; Badshah, Amin; Lal, Bhajan; Murtaza, Shahzad; Chatterjee, Pabitra B.; Akbar, Kamran; Crans, Debbie C.
Abstract : The cover image, by Ataf Altaf et al., is based on the Full Paper Probing of Ferrocenyl Anilines on Model Micelle / Reverse Micelle Membrane and their Enhanced Reactivity for Reactive Oxidants, https://doi.org/10.1002/aoc.4334 .